Influência do ambiente no desenvolvimento de colônias iniciais de formigas cortadeiras (Atta sexdens rubropilosa) - Camargo, Roberto da Silva (2013)
Annually, mature colonies of Atta ants produce winged males and females, where leave the colony in which they were produced to form new colonies and thus continue the species perpetuation. The foundation of Atta spp. colonies always involves high queen effort, solely responsible for growing the fungus and the care with itself and its offspring. During the foundation there is consumption of body reserves. This study investigated how the environment influences the development of newly founded colonies of leaf cutting ant, Atta sexdens rubropilosa. Therefore, it was compared field colonies collected five months after the nuptial flight and colonies maintained in the laboratory since the nuptial flight. It was analyzed the weight and size of the population (number of workers, larvae, pupae and eggs), the workers size, the volume and weight of the fungus garden and queen effort for the nest foundation (lipid content and weight of queens). In comparison to the field colonies, the laboratory colonies showed higher values in the weight and size of population, the volume and weight of the fungus garden. Measures of workers by class size did not vary between colonies from field and laboratory. The queen effort for nest foundation was higher in field colonies, which showed a lower percentage of fat and lower weight compared to laboratory colonies. These results show that the environment has a strong influence on the colonies development during the foundation, as well as on the physiological status of the queens, and therefore the survival, development and success of the colony, it is a reflection of the queen efforts and of the environment conditions.